Optimizing Contact Precautions to Curb the Spread of Antibiotic-resistant Bacteria in Hospitals: A Multicenter Cohort Study to Identify Patient Characteristics and Healthcare Personnel Interactions Associated With Transmission of Methicillin-resistant Staphylococcus aureus. (13th September 2019) - O'Hara, Lyndsay M; Calfee, David P; Miller, Loren G; Pineles, Lisa; Magder, Laurence S; Johnson, J Kristie; Morgan, Daniel J; Harris, Anthony D
Abstract: Background: Healthcare personnel (HCP) acquire antibiotic-resistant bacteria on their gloves and gowns when caring for intensive care unit (ICU) patients. Yet, contact precautions for patients with methicillin-resistant Staphylococcus aureus (MRSA) remains controversial despite existing guidelines. We sought to understand which patients are more likely to transfer MRSA to HCP and to identify which HCP interactions are more likely to lead to glove or gown contamination. Methods: This was a prospective, multicenter cohort study of cultured HCP gloves and gowns for MRSA. Samples were obtained from patients' anterior nares, perianal area, and skin of the chest and arm to assess bacterial burden. Results: Among 402 MRSA-colonized patients with 3982 interactions, we found that HCP gloves and gowns were contaminated with MRSA 14.3% and 5.9% of the time, respectively. Contamination of either gloves or gowns occurred in 16.2% of interactions. Contamination was highest among occupational/physical therapists (odds ratio [OR], 6.96; 95% confidence interval [CI], 3.51, 13.79), respiratory therapists (OR, 5.34; 95% CI, 3.04, 9.39), and when any HCP touched the patient (OR, 2.59; 95% CI, 1.04, 6.51). Touching the endotracheal tube (OR, 1.75; 95% CI, 1.38, 2.19), bedding (OR, 1.43; 95% CI, 1.20, 1.70), and bathing (OR, 1.32; 95% CI, 1.01, 1.75) increased the odds of contamination. We found an association between increasing bacterial burden on the patient and HCP glove or gown contamination. Conclusions: Gloves and gowns are frequently contaminated with MRSA in the ICU. Hospitals may consider using fewer precautions for low-risk interactions and more for high-risk interactions and personnel. Abstract : Sixteen percent of gloves or gowns were contaminated with MRSA when HCP were caring for intensive care unit patients with methicillin-resistant Staphylococcus aureus (MRSA). Being an occupational, physical, or respiratory therapist or touching patients increases the odds of MRSA contamination. Patient MRSA bacterial burden is associated with increased contamination.